2021
DOI: 10.4236/ajibm.2021.116041
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing and Supply Chain Collaboration: Strategy for Higher Firm Performance in Ghana

Abstract: Information sharing (IS) has been considered a vital aspect of supply chain management practices. However, it is inadequate to induce a significant increment in performance, so there is a need for collaboration within the supply chain network arises. This study seeks to determine the position of Information Sharing (IS) practices and Supply Chain Collaboration (SCC) in Firm Performance (FP). The study emphasizes that firms exchange information because of the competitive influence stemming from the business env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To improve the links and other aspects, it is necessary to expand the scope of logistics services and help enterprises better adapt to the reform of the modern economic system. Especially in the "Internet +" era, through the effective application of information technology, the process of supply chain management is more transparent, which greatly reduces problems such as the backlog of goods, delayed delivery, and transportation, and brings more considerable economic benefits to enterprises [16]. Of course, businesses can gain additional profits through this management.…”
Section: Resilience and Risk Of Supply Chain Managementmentioning
confidence: 99%
“…To improve the links and other aspects, it is necessary to expand the scope of logistics services and help enterprises better adapt to the reform of the modern economic system. Especially in the "Internet +" era, through the effective application of information technology, the process of supply chain management is more transparent, which greatly reduces problems such as the backlog of goods, delayed delivery, and transportation, and brings more considerable economic benefits to enterprises [16]. Of course, businesses can gain additional profits through this management.…”
Section: Resilience and Risk Of Supply Chain Managementmentioning
confidence: 99%
“…Our research has a couple of theoretical implications. First, our research has established a theoretical and conceptual framework including the concepts of information sharing, information quality, technological innovation, as compared to previous studies (Baah et al , 2022; Baba et al , 2021; Huo et al , 2021) that have skipped the collective effects of these concepts. Hence, our research contributions are invaluable as it offers both theoretical and empirical proof for the associations between the information processing paradigm and technological innovation, and textile SMEs' performance.…”
Section: Discussionmentioning
confidence: 99%
“…Huo et al (2021) stated that information sharing enhances the flexible performance of a firm supply chain. Baba et al (2021) highlighted that information sharing is a strategic tool for firms that brings firm collaboration which leads to superior performance. Baah et al (2022) studied information sharing and found that it is crucial to sustaining supply chain performance.…”
Section: Information Sharing and Firm Performancementioning
confidence: 99%